2009
DOI: 10.1111/j.1365-2249.2009.04019.x
|View full text |Cite
|
Sign up to set email alerts
|

Lower numbers of circulating natural killer T (NK T) cells in individuals with human T lymphotropic virus type 1 (HTLV-1) associated neurological disease

Abstract: SummaryHuman T lymphotropic virus type 1 (HTLV-1) infects 10-20 million people worldwide. The majority of infected individuals are asymptomatic; however, approximately 3% develop the debilitating neurological disease HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP). There is also currently no cure, vaccine or effective therapy for HTLV-1 infection, and the mechanisms for progression to HAM/TSP remain unclear. NK T cells are an immunoregulatory T cell subset whose frequencies and effector fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 27 publications
0
12
1
3
Order By: Relevance
“…We did not observe any difference in frequency of MAIT cells between asymptomatic carriers and HAM/TSP patients. This is in contrast with what has been reported for iNKT cells, another subset of innate T cells, that were further reduced in HAM/TSP patients[17, 40]. …”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We did not observe any difference in frequency of MAIT cells between asymptomatic carriers and HAM/TSP patients. This is in contrast with what has been reported for iNKT cells, another subset of innate T cells, that were further reduced in HAM/TSP patients[17, 40]. …”
Section: Discussioncontrasting
confidence: 99%
“…The high frequency of HTLV-1-specific IFN-γ-producing CD4+ and CD8+ T cells in the central nervous system (CNS) and in peripheral blood seen in HAM/TSP patients suggest that T-cell responses do not prevent development of disease, contributing instead to the proinflammatory milieu characteristic of HTLV-1 related syndromes[1416]. Other T-cell subsets such as NKT cells were investigated in the context of HTLV-1 infection[17], but many aspects of the immunopathogenesis of HTLV-1 related diseases and why HTLV-1 patients are more susceptible to Mtb are still unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been reported that HTLV-1-infected HAM/TSP patients have lower numbers of NK cells [9] and a decreased activity of NK cells in comparison with ACs [10,11].…”
Section: Introductionmentioning
confidence: 98%
“…Diminished NKT cell‐mediated anti‐tumour responses could also contribute to increased incidence of infection‐related tumours such as Kaposi sarcoma and non‐Hodgkin’s lymphoma in AIDS patients 24 . In another human retrovirus infection, lower numbers of circulating Vα24 + Vβ11 + NKT cells in individuals infected with human T lymphotropic virus type 1 (HTLV‐1) have been demonstrated 31 …”
Section: Discussionmentioning
confidence: 99%